Diagnostics and Renovation of Moisture Affected Historic Buildings - Ksit, Barbara; Szymczak-Graczyk, Anna; Nazarewicz, Bogdan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The work concerns issues related to the diagnostics of moisture in historic buildings. Moisture content is one of the basic physical properties of materials. Excessive and undesirable growth of moisture in masonry causes considerable damage to masonry wall assemblies. It reduces the load-bearing capacity of structural elements, causes difficulties with heating and contributes to the development of mould and fungi. The article describes diagnostic procedures, provides available drying methods for walls in buildings and the applied method of renovation based on the example of damage caused by moisture in an examined historic facility.
Keywords: historic building; diagnostics of masonry; technological moisture; drainage of masonry; renovation; non-invasive methods; invasive method; budynki zabytkowe; ocena murów; zawilgocenie; osuszanie murów; renowacja; metoda nieinwazyjna; metoda inwazyjna